IMPLEMENTASI PEMBUATAN PUPUK KOMPOS MENUJU PERTANIAN BERKELANJUTAN DI DESA AIK BUKAQ KECAMATAN BATUKLIANG UTARA KABUPATEN LOMBOK TENGAH - Dwiguna, Dedi Kusuma; Indrarani, Ni Putu Sylvia; Ismayati, Ismayati; Hati, utiara Indah Permata; Tritama, Ketut Okan Satya; Syahrul , Syahrul (Universitas Mataram, 2024)
Aik Bukaq Village, located in North Batukliang Subdistrict, Central Lombok Regency, faces challenges in maintaining soil fertility and agricultural productivity due to dependence on expensive and environmentally harmful chemical fertilizers. As an eco-friendly solution, composting organic materials such as plant residues, kitchen waste, and animal manure is implemented. This article outlines the preparation, implementation, and evaluation stages of compost production in Aik Bukaq Village. With active community involvement, this initiative aims to increase crop yields, reduce production costs, and maintain ecosystem balance, providing a practical guide for other villages seeking sustainable agriculture practices.